Congestion, Coordination and Matching - Marja-Liisa Halko; Hannu Salonen (Aboa Centre for Economics (ACE), 2008)
We study the existence of pure strategy Nash equilibria in finite congestion and coordination games. Player set is divided into two disjoint groups, called men and women. A man choosing an action a is better off if the number of other men choosing a decreases, or if the number of women choosing a increases. Analogously, a woman becomes better off if more men or fewer women choose the same action as she does. Existence proofs are constructive: we build simple "best reply" algorithms that converge to an equilibrium.
Keywords: C70; C72; C78; D83; 330; congestion; coordination; matching